Kinetic and Thermal Stability of Cobalt(II)-imipramine Complexes - Bhojya Naik, H.S.; Ramappa, P.G. (Asian Journal of Chemistry, 2010)
New six cobalt(II)-imipramine complexes have been thermally explored in great detail to evaluate the kinetic and thermodynamic parameters such as activation energy Ea, preexponential factor In A, enthalpy ΔH, free energy ΔG and entropy ΔS. The enthalpy values and activation energy values are in the range 2.90–139.22 kJ mol–1 and 6.54–9.95 kJ mol–1, respectively.